Effects of dynamic characteristics of a pipe network on indoor temperature of households - Chen, Yadong; Wang, Xiaoxue; Yang, Hua; Duan, Runze; Li, Shaoxiong (Frontiers in Energy Research, 2023)
District heating has always been regarded as a convenient and environmentally friendly heating method. However, the district heating process involves a considerable amount of wasted energy. To improve the operational strategies of heating networks and heating quality, reduce energy waste, promote the sustainable development of resources and cities, it is necessary to investigate the dynamic characteristics of pipe networks. This paper describes the dynamic characteristics of a pipe network in which the intermittent operation of the primary pipe network were adjusted. The effects of the dynamic characteristics of the pipe network on the indoor temperature of households are numerically analyzed. When the primary network stops and the secondary network continues working, the indoor temperature begins to decrease, slowly at first, and then more quickly. The indoor temperature of households in the system remains unchanged for a short period before starting to drop with the increase of the time. It takes about 150–245 min for the indoor temperature in the heating system to drop to 16°C. The smaller the room area, the larger the area of the envelope structure, and the faster the room temperature drops. The higher the intermittent heating temperature, the longer it takes for the indoor temperature to drop to 16°C. An intermittent heating temperature of 5°C or above ensures that every household in the heating system retains an indoor temperature above 16°C after 2 h.